Efficient dehydrogenation of high-concentration formic acid over PdAu/AC-NH2 catalysts without additives under ambient conditions. (13th December 2022) - Jiang, Shuchao; Ren, Guoqing; Yu, Tie
Abstract : An efficient PdAu nanocatalyst was designed for high-concentration formic acid dehydrogenation by optimizing the surface energy and electronic property of Pd. Abstract : Formic acid (FA) is regarded as a promising hydrogen storage material, and designing efficient catalysts for the dehydrogenation of high-concentration FA (HCF) is attractive but challenging. Herein, a catalyst comprising PdAu nanoparticles (NPs) anchored on amine-functionalized commercial active carbon (PdAu/AC-NH2 ) was synthesized and evaluated for the dehydrogenation of HCF without additives under ambient conditions. The Pd3 Au2 /AC-NH2 catalyst exhibits durable performance and 100% H2 selectivity when the FA concentration is ≤5 M and affords an excellent turnover frequency (TOF) of 3300 h −1 for 5 M FA and 603 h −1 for neat FA at 303 K. Subsequent characterizations reveal that the Au content affects the surface energy and electron property of Pd on PdAu alloy nanocatalysts, which play an indispensable role in the rate committed step of HCOO* adsorption and C–H cleavage. Besides, ultrafine PdAu NPs (2.20 nm) and amine groups synergistically accelerate catalyst activity. This work may pave the way for HCF-based high hydrogen density storage under ambient conditions.